Validity and Reliability of Bergen Insomnia Scale (BIS) Among Adolescents - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objective: The aim of this research was to examine validity and reliability of the Turkish version of the Bergen Insomnia Scale (BIS) in adolescents. Methods: The scale was applied to a total of 1293 adolescents and 110 students were retested four weeks later. While content and construct validity analyses were carried out for validity of the scale, internal consistency and test-retest analysis was used for the reliability. Content validity of the scale was evaluated by opinions from 10 experts, construct validity via confirmatory factor analysis, internal consistency via Cronbach's alpha reliability coefficient, test-retest results via Pearson's correlation analysis. Results: Cronbach's alpha reliability coefficient of Bergen Insomnia Scale was found as 0.72. Item - total correlations were >= 0.36 and test-retest correlation was 0.74. Content validity index was found to be 99%, there was agreement between experts, the items in the scale were suitable for our culture, and it represented the structure which was intended to be measured. Confirmatory factor analysis confirmed the structure of BIS consisting of 6 questions and 2 factors. Conclusion: Bergen insomnia scale was found to be reliable and valid. The scale can be used to measure insomnia in Turkish adolescents.
Keywords: Bergen Insomnia Scale; validity; reliability; GENERAL-POPULATION; PREVALENCE; RISK